Una tarea inconclusa? Armonizar la directiva relativa al trabajo en plataformas con el acervo social de la Unión Europa e internacional; An unfinished task? Matching the platform work directive with the EU and international "social acquis" - Antonio Aloisi; Silvia Rainone; Nicola Countouris (Organización Internacional del Trabajo (OIT), 2024)
– Besides straining international, regional and national employment status classification models, digital labour platforms are pioneering new strategies and approaches in terms of algorithmic management, digital surveillance, remote work and cross-border outsourcing, which are increasingly being adopted in more conventional sectors of the economy. Developments in the platform economy are thus crucial in providing a stress test for the resilience of existing labour standards, as well as providing useful input in terms of the reforms needed to ensure their suitability, the collective interest representation and mobilization aspects comprehended by rapidly changing labour markets. This paper seeks to explore the key emerging regulatory dimensions of platform work. It contextualizes the challenges associated with platform work as an expression of the consolidated features that, in the past decades, have been transforming the labour market: non-standardization and the deregulation of employment relationships. Following that, it considers the definition of the personal scope of application as a key challenge faced by essentially all attempts to regulate platform work. It does so primarily by exploring the functions and operations of a legal device known as "presumption of employment", currently being considered by the proposed EU directive on platform work as a key tool to address the complex employment status classification questions that have surrounded the "gig economy" since its emergence. The paper then provides a conceptual cartography of the various EU regulatory instruments (both existing ones and those currently in the legislative pipeline) that will, jointly, define the legal mosaic of labour rights applicable to the heterogeneous phenomenon of platform work in the years to come. The paper suggests that recent regulatory developments reflect a persistent attachment to the dichotomous model of subordination versus autonomy. Even once the EU directive on platform work has been adopted, work relations in this area will not be exhaustively regulated by its provisions and other existing directives and instruments would still provide (and, in some cases, fail to provide) answers to various legal questions (such as the concept of working time, privacy at work and the information and consultation of workers and their representatives) that are central to the rights, and livelihoods, of workers providing their labour through digital platforms. The paper elaborates on the interlinkages, overlaps, and tensions between the EU's regulatory instruments and identifies strengths and weaknesses, and potential areas for further elaboration and even legislative reform. This paper concludes that in order to improve the working conditions of platform workers, regulators need to rethink the traditional rigidities associated with the subordination paradigm.
Keywords: 330; non-standard forms of employment; digital labour; workers; gig economy